Solidarity, Self-Interest and the Unionization Differential Between Europe and North America - Adams, Roy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
In this article, the«  solidarity » argument is questionned on both theoretical and empirical grounds. It is argued instead that the unionization differential between the two continents may be more adequately explained in terms of differences on key dimensions of the existing industrial relations systems.